2004
DOI: 10.1038/sj.leu.2403566
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rasburicase, a recombinant urate oxidase (Elitek™), in the management of malignancy-associated hyperuricemia in pediatric and adult patients: final results of a multicenter compassionate use trial

Abstract: The recombinant urate oxidase, rasburicase (Elitekt, SanofiSynthelabo, Inc.), has recently received regulatory approval for the prevention and treatment of hyperuricemia in children with leukemia, lymphoma, and solid tumors. Prior to approval, 682 children and 387 adults in the US and Canada received rasburicase on compassionate-use basis. Uric acid concentration declined rapidly in both adult and pediatric patients after rasburicase treatment. Similar responses were observed in patients treated with subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(126 citation statements)
references
References 19 publications
3
114
1
4
Order By: Relevance
“…Historically, in studies that did not involve rUO 10% -20% of patients with hematological malignancies required hemodialysis, but a more recent study found that the use of rUO decreased the frequency of hemodialysis to just a few percent [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, in studies that did not involve rUO 10% -20% of patients with hematological malignancies required hemodialysis, but a more recent study found that the use of rUO decreased the frequency of hemodialysis to just a few percent [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although the major cause of ARF is uric acid nephropathy secondary to tumor lysis, hyperphosphatemia also induces severe ARF, which can lead to a requirement for hemodialysis [5]. Hyperkalemia, which can result in severe arrhythmia and sudden death, is another potentially a life-threatening consequence of TLS.…”
Section: Chemosensitivementioning
confidence: 99%
“…The strategy in preventing and treating infectious complications applied the same principles as used in BFM group. 23 Rasburicase, 24 a recombinant urate oxidase, has been available for effective prevention and treatment of leukemia lysis syndrome for the recent 2 years.…”
Section: Supportive Carementioning
confidence: 99%
“…Studies that did not use rUO reported that 10% -20% of patients with hematological malignancies required hemodialysis; however, a more recent study found that the use of rUO decreased the frequency of hemodialysis to just a few percent [7]. Although rUO only affects uric acid levels, progression to hyperphosphatemia, hyperkalemia and DIC should be considered.…”
Section: Discussionmentioning
confidence: 99%